The foreign exchange markets under floating rates : a study in international finance - Baschnagel, Hubert; Group of Thirty (New York : Group of Thirty, 1980)
The book is a summary of the study of group thirty, that emphasized the growth and significance of foreign exchange related activity in the United States, and centered on the New York market.
ahz 10/04/2019
Loans
Keywords: Foreign exchange market; Foreign exchange